1933
DOI: 10.1002/zaac.19332160212
|View full text |Cite
|
Sign up to set email alerts
|

Die spezifischen Wärmen von CaO, Al2O3, CaOċAl2O3, 3CaOċAl2O3, 2CaOċSiO2, 3CaOċSiO2, 2CaOċAl2O3ċSiO2 von 20° bis 1500° C

Abstract: Die spezifischen Wärmen von CaO, Al2O3, CaO·Al2O3, 3CaO·Al2O3, 2CaO·SiO2, 3CaO·SiO2, 2CaO·Al2O3·SiO2 bis 1500° werden mitgeteilt und die Abweichungen vom NEUMANN‐KOPP'schen Gesetz diskutiert. Das NEUMANN‐KOPP'sche Gesetz umfaßt die Erfahrung, daß in vielen Fällen die für die gekoppelten Schwingungen der Verbindungspartner benötigten Energiebeträge ebenso groß sind, wie die durch die Verbindungsbildung — Wachsen des inneren Drucks und damit Zunahme der molekularen Schwingungsfrequenzen — eingesparten Energien.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1940
1940
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Consequently, a value of 40.35 J.mol -1 .K -1 is selected in this work for the absolute entropy of CaO, derived from the DFT phonon calculations in the quasi-harmonic approximation, which is slightly higher than the value of 38.21 J.mol -1 .K -1 compiled in the JANAF tables [41]. Above 300 K, the heat content as a function of temperature as derived from the phonon calculations by Pisch et al [24] were found to be in rather good agreement with most datasets [28,[30][31][32][33][35][36][37], except the heat content proposed by Roth et al [29] and Chekhovskoi et al [34]. Therefore, the latter datasets were not taken into account in the modelling.…”
Section: Review Of the Literature Data 21 Thermodynamic Properties supporting
confidence: 70%
See 2 more Smart Citations
“…Consequently, a value of 40.35 J.mol -1 .K -1 is selected in this work for the absolute entropy of CaO, derived from the DFT phonon calculations in the quasi-harmonic approximation, which is slightly higher than the value of 38.21 J.mol -1 .K -1 compiled in the JANAF tables [41]. Above 300 K, the heat content as a function of temperature as derived from the phonon calculations by Pisch et al [24] were found to be in rather good agreement with most datasets [28,[30][31][32][33][35][36][37], except the heat content proposed by Roth et al [29] and Chekhovskoi et al [34]. Therefore, the latter datasets were not taken into account in the modelling.…”
Section: Review Of the Literature Data 21 Thermodynamic Properties supporting
confidence: 70%
“…The modelled heat content of crystalline CaO are plotted in Fig. 6 along with the available literature data [28][29][30][31][32][33][34]36] and results from previous modellings of the system [17,18]. A satisfactory fit of all the literature data was obtained, expect for the conflicting datasets from Chekhovskoi et al [34] and Roth et al [29].…”
Section: Crystalline Caomentioning
confidence: 71%
See 1 more Smart Citation
“…Above ∼10 GPa the stable phase of CaSiO3 is orthorhombic (space group Pnma), and generally indicated as "Ca-Perovskite" (Ca-Pvsk). For Wo and PWo we adopted the heat capacity coefficients of Berman [42], which are based essentially on the calorimetric measurements of Krupka et al [110,111], White [112], Wagner [113], Elsner von Gronow and Schwiete [114] and disregard the low-to high-wollastonite phase transition detected by Richet et al [104]. We note however that below ∼1000 K the low-wollastonite data of Richet et al [104] are consistent with the heat capacity function selected in this work and a good consistency is observed also for PWo up to ∼2000 K (see Fig.…”
Section: Casio3mentioning
confidence: 99%